Effect of red wine or its polyphenols on induced apical periodontitis in rats - Dal-Fabbro, Renan [UNESP]; Cosme-Silva, Leopoldo; Rezende Silva Martins de Oliveira, Fernanda [UNESP]; Capalbo, Letícia Cabrera [UNESP]; Plazza, Flávia Alfredo [UNESP]; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Gomes-Filho, João Eduardo [UNESP] (Wiley, 2021)
Aim: To evaluate the effect of red wine consumption or its polyphenols on the inflammation/resorption processes associated with apical periodontitis in rats. Methodology: Thirty-two three-month-old Wistar rats had apical periodontitis induced in four first molars and were then arranged into four groups: control (C)—rats with apical periodontitis; wine (W)—rats with apical periodontitis receiving 4.28 ml/kg of red wine; resveratrol+quercetin (R+Q)—rats with apical periodontitis receiving 4.28 ml/kg of a solution containing 1.00 mg/L of quercetin and 0.86 mg/L of resveratrol and alcohol (ALC)—rats with apical periodontitis receiving the alcoholic dose contained in the wine. The oral gavage treatments were administered daily, from day 0 to day 45. On the 15th day, apical periodontitis was induced, and on the 45th day, the animals were euthanized. Histological, immunohistochemical (RANKL, OPG, TRAP, IL-10, TNF-⍺ and IL-1β) and micro-computed tomography for bone resorption analysis were performed in the jaws. The Kruskal–Wallis with Dunn's test was performed for nonparametric data, and the anova with Tukey's test for parametric data, p <.05. Results: The median score of the inflammatory process was significantly lower in the R+Q group (1) compared to the C (2) (p =.0305) and ALC (3) (p =.0003) groups, and not different from the W (1.5) group. The immunolabeling for OPG was significantly higher in the R+Q group (p =.0054) compared to all groups; the same was observed for IL-10 (p =.0185), different from groups C and ALC. The R+Q group had the lowest TRAP cell count (p <.0001), followed by the W group, both inferior to C and ALC groups. The lowest bone resorption value was in the R+Q group (0.50mm3 ± 0.21mm3), significantly lower (p =.0292) than the C group (0.88mm3 ± 0.10mm3). The W group (0.60 mm3 ± 0.25 mm3) and R+Q group had less bone resorption compared to the ALC group (0.97 mm3 ± 0.22 mm3), p =.0297 and p =.0042, respectively. Conclusion: Red wine administration to rats for 15 days before induction of apical periodontitis decreased inflammation, TRAP marking and periapical bone resorption compared to alcohol. Resveratrol-quercetin administration reduced the inflammatory process in apical periodontitis, periapical bone resorption, and altered the OPG, IL-10 and TRAP expression compared to C and ALC groups.
Keywords: periapical periodontitis; polyphenols; quercetin; resveratrol; wine